A Comparative Study of Transulnar and Transradial Artery Access for Percutaneous Coronary Intervention in Patients with Acute Coronary Syndrome. (22nd September 2014) - LIU, JUN; FU, XIANG‐HUA; XUE, LING; WU, WEI‐LI; GU, XIN‐SHUN; LI, SHI‐QIANG
Abstract Objectives Transradial access has become commonly used for elective evaluation of patients with coronary artery disease, but it has some disadvantages and has had limited use in the acute coronary syndrome (ACS). Because the diameter of the ulnar artery is usually larger than that of the radial artery, we hypothesized that the ulnar artery could be used as an access for percutaneous coronary intervention (PCI). The present study compares the feasibility, safety, and outcome of transulnar artery and transradial artery access for PCI in patients with ACS. Methods We reviewed 636 patients who had PCI for ACS from May 2006 to May 2009. The patients were randomly assigned to transulnar intervention (TUI; 317) or transradial intervention (TRI; 319). Results Several outcomes were similar in the TUI and TRI groups: success rate of first puncture, duration of guiding catheter engagement, puncture‐to‐balloon inflation time, final thrombolysis in myocardial grade 3 flow, complications at the vascular access site, and postprocedure complications. The incidence of severe arterial spasm and forearm hematoma in the TUI groups was significantly less than that in the TRI group. At 1‐year follow‐up, the level of blood oxygen saturation at the middle finger and Doppler ultrasonographic characteristics of the ulnar artery did not significantly change from pre‐PCI values for these criteria in either group. Conclusion The TUI approach has results and access complications similar to the TRI approach and is a safe and feasible alternative for ACS patients. (J Interven Cardiol 2014;27:525–530)